Fitness test results of hungarian and international-level soccer referees and assistants - Bartha, C.; Petridis, L.; Hamar, P.; Sandor, C.; Castagna, C. (The Journal of Strength and Conditioning Research, 2009)
The aim of our research was primarily to compare the conditional abilities of European countries' Fédération Internationale de Football Association (FIFA) referees with those of Hungarian national and county referees and, secondly, to investigate whether the stop tests of FIFA and the Union of European Football Associations (UEFA) provide reliable discrimination criteria between the different levels of referees. The main focuses of our research were speed and endurance, which were measured by the stop tests of FIFA and UEFA-namely, 50- and 200-m sprint runs and a 12-minute run, respectively (Cooper test). In our study, the test results of 2459 soccer referees were analyzed; they include the results of the total Hungarian population of referees and the results from 17 different European countries. Referees were classified into 6 different levels according to their qualifications. The results show that in the 12-minute run, FIFA referees covered the longest distance (3043 ± 127 m), followed by the Hungarian elite referees (2939 ± 136 m); less distance was covered by county III-level referees (2522 ± 270 m). Differences between groups in the endurance event were significant (p < 0.05) in all cases. In the sprint runs, there was no difference between FIFA and Hungarian elite referees. In both sprints, FIFA-level and Hungarian elite referees performed the fastest times, and county III-level referees had the slowest times. It can be concluded that the aerobic fitness level demonstrated in the 12-minute run provides the most adequate criteria for discrimination between different competitive levels. Hungarian elite referees, on the basis of their fitness test results, are comparable with international-level referees. The major quality step in a referee's career can be located at the third-division competition level.